Trade relations between the US and China - Bernd Kunze (Intereconomics, 1971)
President Nixon's Intention to visit Peking is attracting tremendous Interest all over the world. The present article discusses past developments of US/Chinese trade and Its possibilities In the future.
Keywords: 330; Foreign trade